Altered sensory feedbacks in pianist's dystonia: the altered auditory feedback paradigm and the glove effect - Cheng, Felicia P.; Grossbach, Michael; Altenmüller, Eckart (Frontiers in Human Neuroscience, 2013)
Background: This study investigates the effect of altered auditory feedback (AAF) in musician's dystonia (MD) and discusses whether altered auditory feedback can be considered as a sensory trick in MD. Furthermore, the effect of AAF is compared with altered tactile feedback, which can serve as a sensory trick in several other forms of focal dystonia. Methods: The method is based on scale analysis (Jabusch et al. 2004). Experiment 1 employs synchronization paradigm: 12 MD patients and 25 healthy pianists had to repeatedly play C-major scales in synchrony with a metronome on a MIDI-piano with 3 auditory feedback conditions: 1. normal feedback; 2. no feedback; 3. constant delayed feedback. Experiment 2 employs synchronization-continuation paradigm: 12 MD patients and 12 healthy pianists had to repeatedly play C-major scales in two phases: first in synchrony with a metronome, secondly continue the established tempo without the metronome. There are 4 experimental conditions, among them 3 are the same altered auditory feedback as in Experiment 1 and 1 is related to altered tactile sensory input. The coefficient of variation of inter-onset intervals of the key depressions was calculated to evaluate fine motor control. Results: In both experiments, the healthy controls and the patients behaved very similarly. There is no difference in the regularity of playing between the two groups under any condition, and neither did AAF nor did altered tactile feedback have a beneficial effect on patients’ fine motor control. Conclusions: The results of the two experiments suggest that in the context of our experimental designs, AAF and altered tactile feedback play a minor role in motor coordination in patients with musicians' dystonia. We propose that altered auditory and tactile feedback do not serve as effective sensory tricks and may not temporarily reduce the symptoms of patients suffering from MD in this experimental context.